2013
DOI: 10.5047/eps.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Gravity variation around Shinmoe-dake volcano from February 2011 through March 2012—Results of continuous absolute gravity observation and repeated hybrid gravity measurements

Abstract: We report here on continuous absolute gravity measurements made between February 2011 and March 2012 and repeated relative gravity measurements in the vicinity of Shinmoe-dake volcano, which commenced erupting in late January 2011. We find that 20 of 24 eruptive events are associated with precursory short-term gravity decreases occurring over 5-6 hours followed by quick recoveries lasting 1-2 hours. Also evident are significant long-term gravity changes arising principally from hydrological processes around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…For example, volcanic activities usually relate to gravity variance. Scientists find that most volcanic eruptive events are associated with precursory gravity decreases occurring over 5-6 h followed by quick recoveries lasting 1-2 h [10]. The amplitude of absolute gravity changing before volcanic eruption could be 10 µGal 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, volcanic activities usually relate to gravity variance. Scientists find that most volcanic eruptive events are associated with precursory gravity decreases occurring over 5-6 h followed by quick recoveries lasting 1-2 h [10]. The amplitude of absolute gravity changing before volcanic eruption could be 10 µGal 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, volcanic activities may be predicted by continuous absolute gravity measurements. Scientists found that quick gravity decreasing and recovering of about 10 μGal occurred before most volcanic eruption events [2] . On the other hand, accurate absolute gravity measurements also play an important role in hydrological observations.…”
mentioning
confidence: 99%